Synthesis of networks on chips for 3D systems on chips - Murali, Srinivasan; Seiculescu, Ciprian; Benini, Luca; De Micheli, Giovanni (Proceedings of the 2009 Asia and South Pacific Design Automation Conference, 2009)
Three-dimensional stacking of silicon layers is emerging as a promising solution to handle the design complexity and heterogeneity of Systems on Chips (SoCs). Networks on Chips (NoCs) are necessary to efficiently handle the 3D interconnect complexity. Designing power efficient NoCs for 3D SoCs that satisfy the application performance requirements, while satisfying the 3D technology constraints is a big challenge. In this work, we address this problem and present a synthesis approach for designing power-performance efficient 3D NoCs. We present methods to determine the best topology, compute paths and perform placement of the NoC components in each 3D layer. We perform experiments on varied, realistic SoC benchmarks to validate the methods and also perform a comparative study of the resulting 3D NoC designs with 3D optimized mesh topologies. The NoCs designed by our synthesis method results in large interconnect power reduction (average of 38%) and latency reduction (average of 25%) when compared to traditional NoC designs.